(untitled) (Medico Legal Update, 2021)
After delivery uterine function usually exposed by bacterial contamination of the uterine lumen. This study was conducted on 21 cows of Holstein-Friesian breed, aged between 4-6 years, with parity of 2-4 times suffered from postpartum metritis. The disease diagnosed according to the clinical symptoms and vaginal examination. Animals divided into 3 equal groups. 1st group treated with PGF2? 20 mg/im., 2nd group treated with 2% lugol’s Iodine Intra Uterine, while the 3rd group treated with lotagen 2% I.U. The results showed that the treatment with PGF2? give high efficacy rate 100% (7/7) than that with lugol’s Iodine 57% (4/7) and with lotagen 71% (5/7). There was a significant difference (P?0.05) in treatment with PGF2? as compared with other treatments, it was concluded from this study that PGF2? give the best results in postpartum metritis treatment.